EFEKTIVITAS EKSRTAK JAHE UNTUK MENGURANGI EMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER 1 DI KLINIK Hj. DEWI SESMERA MEDAN - Fina Kusuma Wardani; Nurrahmaton Nurrahmaton; Sri Juliani (Universitas Prima Indonesia, 2020)
Gravidarum emesis is a natural thing to experience during pregnancy in the first trimester, and will experience gravidrumpeal hemorrhoid 6 after the last day of pregnancy. As for the treatment of emesis, the drug is extracted from herbal extracts. By consuming extracts 2 times a day, the day and day for 4 days according to the goals. Research To find out the effectiveness of the ginger to reduce gravidar hemesis in the first trimester of pregnancy. research design was a type of experimental research, Design of this study used posttest without control study. Sample technique takes a total sample of your population with 30 people. Using Wilcoxon test to find out the effectivity of the ginger on memesis gravidarum. The research results, it can be seen that from 30 respondents, majority of them are gravidarum respondents, there are 13 respondents (43.3%) and minority groups are 5 respondents (16.7%). ) and a minority of 8 respondents (26.7%) with a p-value = 0.000 (p <0.05). The conclusion of the influence of breeding extracts to reduce gravidarumpada episodes in the first trimester in Hj Sesmera clinic Medan.